A Voluntary Statewide Newborn Screening Pilot for Spinal Muscular Atrophy: Results from Early Check - Katerina S. Kucera; Jennifer L. Taylor; Veronica R. Robles; Kristin Clinard; Brooke Migliore; Beth Lincoln Boyea; Katherine C. Okoniewski; Martin Duparc; Catherine W. Rehder; Scott M. Shone; Zheng Fan; Melissa Raspa; et al. (MDPI AG, 2021)
Prior to statewide newborn screening (NBS) for spinal muscular atrophy (SMA) in North Carolina, U.S.A., we offered voluntary screening through the Early Check (EC) research study. Here, we describe the EC experience from October 2018 through December 2020. We enrolled a total of 12,065 newborns and identified one newborn with 0 copies of SMN1 and two copies of SMN2, consistent with severe early onset of SMA. We also detected one false positive result, likely stemming from an unrelated blood disorder associated with a low white blood cell count. We evaluated the timing of NBS for babies enrolled prenatally (n = 932) and postnatally (n = 11,133) and reasons for delays in screening and reporting. Although prenatal enrollment led to faster return of results (median = 13 days after birth), results for babies enrolled postnatally were still available within a timeframe (median = 21 days after birth) that allowed the opportunity to receive essential treatment early in life. We evaluated an SMA q-PCR screening method at two separate time points, confirming the robustness of the assay. The pilot project provided important information about SMA screening in anticipation of forthcoming statewide expansion as part of regular NBS.